Electricity production from lignin photocatalytic degradation byproducts. (15th September 2016) - Shewa, Wudneh Ayele; Lalman, Jerald A.; Chaganti, Subba Rao; Heath, Daniel D.
Abstract: Byproducts from a photocatalytic pretreated model lignin chemical, sodium LS (lignosulfonate), was used to produce electricity in SCMFCs (single chamber microbial fuel cells). Pretreating LS was performed using TiO2 -UV photocatalysis. Optimization and modeling of the photocatalytic degradation process was performed using the Box-Behnken design method to achieve a maximum BOD5 to COD ratio. LC-MS (Liquid chromatography–mass spectrometry) analysis was conducted to identify compounds produced from the photocatalysis of LS. The biofilm microbial diversity and performance of SCMFCs fed PrLS (pretreated LS) was compared to SCMFCs fed glucose at the same COD loadings and operating conditions. The PrLS fed SCMFCs, operated at 37 ± 1 °C, generated maximum current and power densities of 6556 ± 360 mA m −3 and 1881 ± 103 mW m −3, respectively. The corresponding maximum current and power densities normalized to the cathode area were 868 ± 48 mA m −2 and 248 ± 14 mW m −2, respectively. The SCMFCs removed 77.6 ± 2.3% of the COD of the PrLS and achieved a coulombic efficiency of 17.7 ± 1.2%. This study demonstrated the effectiveness of photocatalysis coupled with a bioelectrochemical system in treating lignin compounds and simultaneously generate electricity. Graphical abstract: Highlights: Photo and bioelectrochemical conversion of model lignin chemical into electricity. Optimize the photocatalytic process performed using a Box-Behnken design. Microbial diversity of bioelectrochemical fuel cell.